2010
DOI: 10.1163/156856209x435835
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Film as a Novel Post-Surgical Tissue Adhesion Barrier

Abstract: In this study, we focused on alginate as a physical tissue adhesion barrier material. The alginate has a muco-adhesive property in the solid state and becomes a viscous slippery gel-like solution in the dissolved state. We hypothesized that the alginate film without cross-linking can be a good candidate as a tissue adhesion barrier. The un-cross-linked alginate film may stably adhere onto a wound owing to its muco-adhesive property and, thus, does not need suturing to fix it, and then the film may slowly chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…As compared to results recently published in the literature using Adept® (Baxter Healthcare Corporation, USA) [28,29,30,31,32,33], Interceed® (Ethicon, Inc., USA) [25,27,29,34,35,36,37,38,39], and Seprafilm® (Genzyme Corporation, USA) [26,27,31,34,38,39,40,41,42,43,44] in rat models, the results obtained with 4DryField PH in this study are in the upper range of benefit and are comparable with the data of Kaptanoglu et al [43] and Wallwiener et al [29]. …”
Section: Discussionmentioning
confidence: 96%
“…As compared to results recently published in the literature using Adept® (Baxter Healthcare Corporation, USA) [28,29,30,31,32,33], Interceed® (Ethicon, Inc., USA) [25,27,29,34,35,36,37,38,39], and Seprafilm® (Genzyme Corporation, USA) [26,27,31,34,38,39,40,41,42,43,44] in rat models, the results obtained with 4DryField PH in this study are in the upper range of benefit and are comparable with the data of Kaptanoglu et al [43] and Wallwiener et al [29]. …”
Section: Discussionmentioning
confidence: 96%
“…Alginate, already used as a wound dressing agent, has hemostatic and antimicrobial effects in its calcium or sodium form, and has been shown to prevent adhesion formation in animal studies [47,48]. ACH had a comparable efficacy to CH in terms of adhesion rate and severity, although, in the case of no prior IUA, intrauterine application of ACH after hysteroscopic surgery resulted in lower de novo IUA compared with CH.…”
Section: Ch Gelmentioning
confidence: 99%
“…Alginate, the most widely used material for microbead formation 36 , is a naturally occurring anionic polysaccharide derived from brown algae that also has desirable properties for SWNT encapsulation. Alginate has been approved for wound dressings and as a cell carrier due to its lack of toxicity 3739 , however it has been found that the ionically bonded hydrogels frequently suffer from degradation, unable to endure the mechanical and chemical strain of implantation and the exchange of cations that occurs under physiological conditions 36,40,41 . Although ionically crosslinked alginate gels can undergo uncontrollable biodegradation while releasing polysaccharide chains from their matrix 42 , partial control can be obtained by bimodal molecular weight distribution of the polymer building blocks 43 .…”
mentioning
confidence: 99%